Eksplorasi pembelajaran berbasis teknologi di sekolah dasar Indonesia - Ridha Hidayani; Arief Rachman Hakim (Universitas Pendidikan Indonesia, 2026)
The significant transformation in the world of education has encouraged teachers to integrate technology to improve the quality of learning. This study aims to examine the types of technology and patterns of technology integration in learning in elementary schools in Indonesia. This study uses a Systematic Literature Review (SLR) approach to publications from the last 5 years. Of the 98 articles reviewed, 42 articles met the inclusion criteria for analysis. The results of the study show that the types of technology used in elementary school learning are divided into eight technology groups, namely interactive digital learning media, digital-based evaluation and training applications, structured digital teaching materials, online Learning Management System (LMS), online learning conference platforms, concept visualization media, Augmented Reality (AR) technology, and supporting ICT devices. Learning integration patterns are divided into five patterns, namely technology as a medium for delivering material, technology as a means of training and learning assessment, technology in model-based learning, technology for collaborative learning, and technology through classroom devices. A more comprehensive integration of technology into learning can facilitate greater access to learning and encourage the implementation of the Kurikulum Merdeka, which currently emphasizes a mindful, meaningful, and joyful learning process.